Nonlinear Analysis of Slender Steel Beams (Proceedings of Faculty of Civil Engineering, 2019)
The behavior of the slender web plate of the welded unstiffened beam under uniformly distributed vertical load was analyzed in this paper. A numerical model of the beam was created in the ABAQUS program. The aim of this paper is to get a faithful numerical simulation of the beam behavior compared to the laboratory-tested beam whose test results are taken from the literature and analyze the occurrence of buckling in the zone of web panel. Linear analysis was used to determine the buckling eigenvalue of the beam and nonlinear analysis was used to deformation values of the beam. Finally, the comparison between the results obtained by numerical simulations with the results of laboratory tests were carried out.